Exploring The Mediating Role of Complaint Resolution in The Relationship Between Excellent Service, Competitive Advantage, and Customer Loyalty - Untung Murdiyanto; Johannes; Ilham Wahyudi (Fundamental and Applied Management Journal, 2026)
This study investigates the determinants of customer loyalty in the port service industry by examining the direct and indirect effects of Excellent Service and Competitive Advantage on Customer Loyalty, with Complaint Resolution as a mediating variable. Anchored in Utility Theory, Customer Loyalty Theory, and Competitive Advantage Theory, the research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data collected from clients of PT Pelabuhan Indonesia (Persero) Regional 2. The findings reveal that both Excellent Service and Competitive Advantage significantly influence customer loyalty. However, Competitive Advantage alone does not suffice to build long-term loyalty unless supported by effective complaint resolution mechanisms. The mediating role of Complaint Resolution is found to be statistically significant, underscoring the importance of responsive and fair grievance handling systems in enhancing customer retention. These results suggest that in a competitive service environment such as port operations, fostering loyalty requires not only continuous service innovation and operational efficiency but also a strategic commitment to customer-oriented problem solving. The study contributes to the growing body of literature on service loyalty in the maritime logistics sector and offers practical implications for service improvement and relationship management in port service enterprises.